EFISIENSI SEKTOR PUBLIK SULAWESI SELATAN DENGAN TEKNIK PENDEKATAN DATA ENVELOPMENT ANALYSIS - Adhilla, Miftaqhul; Alam, Syamsu; Kamaruddin, Citra Ayni (Bisnis-Net, 2025)
Unemployment is a major problem facing Indonesia. High unemployment has a direct and indirect effect on poverty caused by someone not having a job and income, crime that is prone to be committed by someone to meet their needs illegally and political problems. This study focuses on the efficiency of the public sector of regencies/cities in South Sulawesi. This study uses secondary data from non-managerial agencies and regional annual reports. Input and output variables are quantitative data, so this study is quantitative. The DEA calculation model is carried out by identifying input and output. One of the analysis methods used to assess DMU efficiency is DEA (Data Development Analysis). The input variables are PAD and balancing funds, the output variables are people working and GRDP, and DMU is the Regency/City of South Sulawesi Province. Based on DEAP data on public sector efficiency in South Sulawesi in 2022, only four regencies, namely Bantaeng, Takalar, Pangkep, and Barru, have 100% efficiency.